External Communication Strategies in Supporting School Reputation within Educational Institutions - Rini Solehah Wulandari; Diningrum Citraningsih (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2026)
This study aims to analyze the external communication strategy implemented by Ma'had Aly Alfurqon to support and improve the school's reputation in the community through program planning, organizational formation, program implementation, and activity evaluation. This study uses a qualitative approach with descriptive methods through observation, interviews, and documentation techniques. The results of the study indicate that the external communication strategy is carried out through program planning that is prepared based on the needs of the institution and the development of digital media. The formation of public relations and multimedia organizations is carried out to increase the effectiveness of publications and information dissemination to the community. Program implementation is realized through the use of social media, educational institution outreach to various schools, holding seminars, daurah, general studies, community service, and social and da'wah activities. These programs aim to build a positive image of the institution and improve relations with the community. Program evaluations are conducted periodically to assess the effectiveness of activities and identify various obstacles in their implementation.